THE CRIMINALISATION OF “REVENGE PORN” IN SOUTH AFRICA - Melody Musoni (Obiter, 2019)
This article aims to give an overview of the growing problem of non-consensual pornography in the digital age. The problem of non-consensual pornography grew exponentially when Hunter Moore created a website called IsAnyoneUp.com and started receiving nude images from scornful ex-lovers who posted them on his website. The article discusses the shortcomings of the legal framework that is designed to address non-consensual pornography. In addition, it discusses the provisions in the Cybercrimes Bill 2017 as it relates to criminalisation of non- consensual pornography.